Assessment of performance and comparison of three commercial HDV RNA detection assays: implications for diagnosis and treatment monitoring - Illescas-López, Marta; Chaves-Blanco, Lucía; de Salazar, Adolfo; Hernández-Febles, Melisa; Carracedo, Raquel; Lagarejos, Eduardo; Fuentes, Ana; Pereira, Sara; Cea, Maria; De La Iglesia, Alberto; Freyre, Carolina; Iborra, Asunción; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Objectives Precise HDV-RNA detection and quantification are pivotal for diagnosis and monitoring of response to newly approved treatment. We evaluate the performance of three HDV RNA detection and quantification assays. Methods Hepatitis Delta RT-PCR system kit, EurobioPlex HDV assay, and RoboGene HDV RNA Quantification kit 2.0 were used for testing 151 HBsAg-positive samples, 90 HDV-RNA negative and 61 HDV-RNA positive. We also evaluated serial dilutions of the WHO international standard for HDV, PEI 7657/12. All HDV-RNA positive samples were genotyped using a next-generation sequencing strategy. Results Qualitative results indicated a 100% concordance between tests. Quantitative results correlated well, r2 = 0.703 (Vircell-vs-Eurobio), r2 = 0.833 (Vircell-vs-RoboGene), r2 = 0.835 (Robogene-vs-Eurobio). Bias index was 2.083 (Vircell-vs-Eurobio), -1.283 (Vircell-vs-RoboGene), and -3.36 (Robogene-vs-Eurobio). Using the WHO IS, Vircell overestimated the viral load by 0.98 log IU/mL, Eurobio by 1.46 log IU/mL, and RoboGene underestimated it by 0.98 log IU/mL. Fifty-nine samples were successfully genotyped (Genotype 1, n=52; Genotype 5, n=7; Genotype 6, n=1), with similar results for correlation and bias. Conclusion This study underscores the necessity of using reliable HDV-RNA detection and quantification assays, as evidenced by the high concordance rates in qualitative detection and the observed variability in quantitative results. These findings highlight the importance of consistent assay use in clinical practice to ensure accurate diagnosis and effective treatment monitoring of HDV infection.